Differentiation between Normal and Abnormal Cases by Maximum Frequencies of Images of Breast Tissues - Attia, Salim J.; Abood, Ziad M.; Agool, Ibrahim R. (European Journal of Applied Sciences, 2019)
This study focuses on detection of the abnormality of various digital images taken from breast tissues and applying of maximum frequency calculation. It is found that this method gave good result to get the goal of research. The images were calculated for comparing between normal images and abnormal images by maximum values that each cells image reach to. Collection of 100 images is chosen to apply this method. Many research deal with this state [1][2][3][4].